Principle of Goals, Content, and Sequencing: A Review of English for Vocational High School in 2013 Curriculum (2017 Revision) - Annisa Ratna Purwanti (UICELL, 2018)
This qualitative study tries to conform the principle of goals, content, and sequencing in 2013 curriculum (K13) for grade X of VHS. K13 is expected to deal with the 21st century skills which do not only make the students excellent in cognitive domain but also affective and psychomotor domains. That is why K13 has four core competences (KI 1- KI 4) to cover those domains as one of its goals. Another goal is to implement and integrate the language system, macro-skills, and micro-skills. K13 also aims to create communicative and meaningful activities. The strengths in sequencing content in K13 are the way it constructs the content starts from the easy to the difficult materials and it models a spiral curriculum. Despite the goals and content in K13 bring more positive development rather its predecessor, it also has several issues dealing with this principle. They are divided into issues in sequencing goals and sequencing content. The issues are related because the development of content is derived from goals. Issues in goals are the concept of communicative and meaningful teaching learning and time allotment. While the issue discovered in sequencing content is authenticity. The researcher also gives suggestion dealing with the issues.